Design Evolution: From Rolling Piston to Revolving Vane to Cross-Vane Expander-compressor unit - Ooi, Kim Tiow (2016)
In this paper the design evolution from rolling piston compressor (RP) to revolving vane compressor (RV) and finally to cross-vane expander-compressor unit (CVEC) is presented and discussed. The details in the design philosophy which initiated this evolution will be presented and discussed. It is estimated that more than 90% of the room air-conditioners uses RP in its compressor. This is because of its advantages: it has the few parts, it is simple geometrically and it is reliable. However, it is with no weaknesses. RP's weaknesses lie in three parts: too many rubbing surfaces with high relative rubbing velocity with each other which give rise to high frictional losses; components (eccentric and roller) are not rotating at their centres and resulted in unnecessary inherent vibration; vane tip is constantly rubbing against the roller making it a weakest part in design. To overcome RP's weaknesses, RV is introduced. As compared to RP, RV has fewer rubbing surfaces, and the relative velocities among these surfaces are reduced Components in RV rotate at their own centres and there is no inherent vibration; the rubbing at the vane tip has been eliminated completely. However, like RP, RV also has a large rotor which occupied "useful" space and making the working chamber relatively small. To overcome this latter problem, CVEC is introduced. In this newly invented CVCE, not only parts are all concentric and rotate at their own centres, the unit also recovers expansion energy and hence significantly reduces energy required by the refrigeration systems. And, more importantly, all these are carried out not at the expense of the additional cost. In this paper, details on these three compressors are explained, compared and their respective uniqueness are shown and discussed.